Evaluation of the Impact of the LPBF Manufacturing Conditions on Microstructure and Corrosion Behaviour in 3.5 wt.% NaCl of the WE43 Magnesium Alloy - de la Pezuela, Jorge; Sánchez-Gil, Sara; Fernández-Hernán, Juan Pablo; Michalcova, Alena; Rodrigo, Pilar; López, Maria Dolores; Torres, Belén; Rams, Joaquín (Materials (Basel, Switzerland), 2025)
This work expands the processing window of the laser powder bed fusion (LPBF) processing of WE43 magnesium alloy by evaluating laser powers and scanning speeds up to 400 W and 1200 mm/s, and their effect on densification, microstructure, and electrochemical performance. Relative density of 99.9% was achieved for 300 W and 800 mm/s, showing that the use of high laser power is not a limitation for the manufacturing of Mg alloys, as has been usually considered. Microstructural characterisation revealed refined grains and the presence of RE-rich intermetallic particles, while microhardness increased with height due to thermal gradients. Electrochemical testing in 3.5 wt.% NaCl solution, a more aggressive media than those already used, indicated that the corrosion of samples with density values below 99% is conditioned by the porosity; however, above this value, in the WE43, the corrosion evolution is more related to the microstructure of the samples, according to electrochemical evaluation. This study demonstrates the viability of high-energy LPBF processing for WE43, offering optimised mechanical and corrosion properties for biomedical and structural applications.
Keywords: magnesium; WE43; corrosion; additive manufacturing; laser powder bed fusion